Cost‐effectiveness of sialendoscopy versus medical management for radioiodine‐induced sialadenitis. (30th March 2018) - Kowalczyk, David M.; Jordan, J. Randall; Stringer, Scott P.
Abstract : Objectives/Hypothesis: The medical management and radiographic identification of radioiodine‐induced sialadenitis (RAIS) is challenging. This study utilizes a cost‐effectiveness analysis to compare upfront sialendoscopy as both a diagnostic and therapeutic option versus multiple modalities of diagnostic radiography along with medical management. Study Design: Literature review and cost‐effectiveness analysis. Methods: A literature review was performed to identify the outcomes of medical management, sialendoscopy, diagnostic radiography, and surgical complications. All charges were obtained from the University of Mississippi Budget Office in 2017 US dollars and converted to costs using the 2017 Medicare Cost‐to‐Charge Ratio for urban medical centers. A cost‐effectiveness analysis was used to evaluate the four treatment arms—sialendoscopy, medical management– ultrasound, medical management–computed tomography (CT) sialography, and medical management–magnetic resonance (MR) sialography. Sensitivity analyses were used to evaluate the confidence levels of the economic evaluation. Results: The incremental cost‐effectiveness ratio for upfront sialendoscopy versus medical management–ultrasound was $30, 402.30, which demonstrates that sialendoscopy is the more cost‐effective option given a willingness‐to‐pay threshold of $50, 000. The probability that this decision is correct at a willingness‐to‐pay of $50, 000 is 64.5%. Sialendoscopic improvement was the most sensitive variable requiring a threshold of 0.70. Of the three imaging modalities, ultrasound dominated MR and CT sialography, both of which required a willingness‐to‐pay of greater than $90, 000 to realize a difference. Conclusions: Upfront sialendoscopy is more cost‐effective compared to medical management utilizing diagnostic ultrasound assuming a willingness‐to‐pay threshold of $50, 000. There is a clear cost‐effectiveness to using ultrasound with medical management over CT and MR sialography in the diagnosis and management of RAIS. Level of Evidence: NA. Laryngoscope, 1822–1828, 2018